Spectrum of infectious dermatoses in pediatric population attending tertiary care centers in Central India: an observational study - Shah, Akhil; Sharma, Parikshit; Singh Bhati, Surendra; Tomar, Anushtha; Jain, Shubhang (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Pediatric infectious dermatoses are distinct group of disorders, comprising of skin problems encountered during childhood and adolescence. There is variation in the pattern and presentation of dermatoses in childhood compared to adults. Aims & Objectives: To determine the prevalence and clinical characteristics of different infectious pediatric dermatoses in rural tertiary care centers in central India. Materials &Methods: This is a cross-sectional study of infectious dermatoses in pediatric patients attending DVL OPD of tertiary care centers, Index Medical College Hospital & Research Center, Indore (M.P.) & Amaltas Institute of Medical Sciences, Dewas (M.P.) between JULY 2018toNOV 2019. Results: There were 106 boys and 94 girls in total 200 study populations. Over all most common infections in the present study were Molluscum contagiosum (14.5%), Pityriasis versicolor (14%) and Tinea corporis (14%). Majority of the infectious skin conditions were Fungal infections (48%) among which most common was dermatophytosis (58.33% of fungal infections) followed by Pityriasis versicolor (29.16% of fungal infections). Viral infections comprised of 37% of all infections among which the most common is Molluscum contagiosum (39.1%) followed by Viral warts (21.6%) and Pityriasis rosea (14.86%). Bacterial infections were 15% of all the infections. Most common bacterial infection was Furunculosis (30%) followed by Impetigo (23.33%) and Secondary pyoderma (20%). Conclusion: The present study was aimed at studying the spectrum of infectious dermatoses in pediatric population in a rural health setup. The present study showed upward trend in fungal infections and downward trend in bacterial infections.